Dickkopf 1 impairs the tumor response to PD-1 blockade by inactivating CD8+ T cells in deficient mismatch repair colorectal cancer. Issue 3 (29th March 2021) - Sui, Qiaoqi; Liu, Dingxin; Jiang, Wu; Tang, Jinghua; Kong, Lingheng; Han, Kai; Liao, Leen; Li, Yuan; Ou, Qingjian; Xiao, Binyi; Liu, Guochen; Ling, Yihong; et al.
Abstract : Background: Dickkopf 1 (DKK1) is associated with tumor progression. However, whether DKK1 influences the tumor response to programmed cell death protein 1 (PD-1) blockade in colorectal cancers (CRCs) with deficient mismatch repair (dMMR) or microsatellite instability (MSI) has never been clarified. Methods: Tumor tissues from 80 patients with dMMR CRC were evaluated for DKK1 expression and immune status via immunohistochemistry. Serum DKK1 was measured in another set of 43 patients who received PD-1 blockade therapy. CT26 cells and dMMR CRC organoids were cocultured with T cells, and CT26-grafted BALB/c mice were also constructed. T-cell cytotoxicity was assessed by apoptosis assays and flow cytometry. The pathway through which DKK1 regulates CD8+ T cells was investigated using RNA sequencing, and chromatin immunoprecipitation and luciferase reporter assays were conducted to determine the downstream transcription factors of DKK1. Results: Elevated DKK1 expression was associated with recurrence and decreased CD8+ T-cell infiltration in dMMR CRCs, and patients with high-serum DKK1 had a poor response to PD-1 blockade. RNA interference or neutralization of DKK1 in CRC cells enhanced CD8+ T-cell cytotoxicity, while DKK1 decreased T-bet expression and activated GSK3β in CD8+ T cells. In addition, E2F1, a downstream transcription factor of GSK3β, directly upregulated T-bet expression. In organoid models, the proportion of apoptotic cells was elevated after individual neutralization of PD-1 or DKK1 and was further increased on combined neutralization of PD-1 and DKK1. Conclusions: DKK1 suppressed the antitumor immune reaction through the GSK3β/E2F1/T-bet axis in CD8+ T cells. Elevated serum DKK1 predicted poor tumor response to PD-1 blockade in dMMR/MSI CRCs, and DKK1 neutralization may restore sensitivity to PD-1 blockade.